Optimasi Ekstraksi Oleoresin Pala (Myristica fragrans Houtt) Asal Maluku Utara Menggunakan Response Surface Methodology (RSM) - Muhammad Assagaf; Pudji Hastuti; Chusnul Hidayat; Supriyadi Supriyadi (agriTECH, 2012)
The purpose of this study was to obtain the optimum extraction conditions by performing the optimization of temperature and extraction time and characterization of constituent chemical components of oleoresin nutmeg (Myristica fragrans Houtt) Origin of North Maluku. Oleoresin extracted using maceration method, for optimization of extraction conditions was done by using Response Surface Methodology (RSM) design with the Central Composite Design (CCD) two factors X1 (temperature / oC) and X2 (times / minute). As for the characterization of the chemical constituent components of nutmeg oleoresin used GC-MS. From the results obtained by the optimization of extraction conditions for extracting the optimum temperature of 51.98 °C and the optimum extraction time was 273.82 minutes with the results for the optimum result of oleoresin obtained by 14.88%. The results of characterization by using GC-MS obtained with 39 components making up oleoresin chemical compound with the largest relative area of the compound methyleugenol (33,397%), myristicine (10,898%), cis-methyl isoeugenol (9,086%), elemicin (8,329% ), and isocoumarin (5,608%) with 34 percent of the components that have relatively minor area.ABSTRAKTujuan dari penelitian ini adalah untuk memperoleh kondisi ekstraksi yang optimum dengan melakukan optimasi suhu dan lama ekstraksi dan karakterisasi komponen kimia penyusun oleoresin pala (Myristica fragrans Houtt) Asal Maluku Utara. Oleoresin diekstrak menggunakan metode maserasi, untuk optimasi kondisi ekstraksi dilakukan dengan menggunakan metode Response Surface Methodology (RSM) dengan disain rancangan Central Composite Design (CCD) dua faktor yaitu X1 (suhu/oC) dan X2 (waktu/menit). Sedangkan untuk karakterisasi komponen senyawa kimia penyusun oleoresin pala digunakan GC-MS. Hasil optimasi kondisi ekstraksi diperoleh suhu optimum ekstraksi sebesar  51,98oC dan waktu optimum ekstraksi adalah selama 273,82 menit dengan hasil optimum hasil oleoresin yang diperoleh sebesar 14,88 %. Hasil karakterisasi dengan menggunakan GC-MS diperoleh 39 komponen dengan 5 senyawa kimia penyusun oleoresin dengan luas area relatif terbesar yaitu senyawa methyleugenol (33.397%), myristicine (10.898%), cis-methyl isoeugenol (9.086%), elemicin (8.329%), dan isocoumarin (5.608%) dengan 34 komponen  yang memiliki persen relatif luas area minor.